2005
DOI: 10.1093/toxsci/kfi136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In Utero and Lactational TCDD Exposure on Bone Development in Differentially Sensitive Rat Lines

Abstract: 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a notorious model compound of highly toxic environmental pollutants, polychlorinated dibenzo-p-dioxins (PCDDs). Their toxic effects are mediated via cytosolic aryl hydrocarbon receptor (AHR). We studied the effects of several dose levels of TCDD on developing rat bone after maternal exposure at different times of gestation and lactation in three differentially sensitive rat lines. Rat lines A, B, and C differ in their sensitivity to TCDD due to mutated AHR (Ahr(hw)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 39 publications
9
60
0
Order By: Relevance
“…In contrast, the female offspring (ewes) exhibited no changes in pQCT variables but the three-point bending test, however, showed that the exposed ewes in the present study had more fragile bone (lower load at failure and reduced stiffness) than the C ewes. Similar reductions in bone strength have been reported previously in studies of rats exposed to dioxin and dioxin like PCBs (Jamsa et al, 2001;Lind et al, 2000b;Miettinen et al, 2005) and a PCB mixture (Andrews, 1989).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, the female offspring (ewes) exhibited no changes in pQCT variables but the three-point bending test, however, showed that the exposed ewes in the present study had more fragile bone (lower load at failure and reduced stiffness) than the C ewes. Similar reductions in bone strength have been reported previously in studies of rats exposed to dioxin and dioxin like PCBs (Jamsa et al, 2001;Lind et al, 2000b;Miettinen et al, 2005) and a PCB mixture (Andrews, 1989).…”
Section: Discussionsupporting
confidence: 86%
“…Since many EDCs have oestrogenic effects, the potential significance of increasing exposure to environmental oestrogens with respect to bone density is of public health interest. Evidence of effects on bone structure of exposure to a range of pollutant classes has been derived, in part, from empirical studies designed to investigate effects of exposure and mechanisms of action using laboratory animals Hermsen et al, 2008;Jamsa et al, 2001;Lind et al, 1999;Lind et al, 2000b;Miettinen et al, 2005;Yilmaz et al, 2006) and domestic animals (Lundberg et al, 2006). Most of these studies concern exposure to abnormally high concentrations of the chemicals concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental exposure to TCDD in rats adversely affects the structural and mechanical properties of bone (Miettinen et al, 2005), and numerous in vitro studies have confirmed TCDD-mediated inhibition of osteoblast differentiation in murine cell models (Gierthy et al, 1994;Korkalainen et al, 2009;Ryan et al, 2007;Singh et al, 2000;Yu et al, 2014). In humans, elevated exposure to polychlorinated dibenzo-p-dioxins and furans during breastfeeding has been strongly associated with hypomineralization of teeth (Alaluusua et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of PCB (Andrews, 1989;Hoffman et al, 1996;Lind et al, 1999Lind et al, , 2000Lundberg et al, 2006) and PCDD (Jämsä et al, 2001;Miettinen et al, 2005) on bone tissue include decreased length and cross-sectional area, alterations in mineral density, and decreased strength following controlled exposure. The mineral density of skull bones of East Greenland polar bears was negatively related to PCBs, polybrominated diphenyl ethers (PBDEs), and other organohalogen pollutants (Sonne et al, 2004).…”
Section: Locationmentioning
confidence: 99%
“…The metals cadmium (Bhattacharyya et al, 1988), aluminum (Hahn, 1989;Firling et al, 1999), and lead (Potula et al, 2006) are known to induce harmful effects on bone tissue. Experimental studies suggest that bone tissue could be an important target for a number of endocrine-disrupting persistent organohalogen pollutants, including hexachlorobenzene (Andrews et al, 1988), polychlorinated biphenyls (PCBs) (Andrews, 1989;Hoffman et al, 1996;Lind et al, 1999Lind et al, , 2000Lundberg et al, 2006), and polychlorinated dibenzo-p-dioxins (PCDD) (Jämsä et al, 2001;Miettinen et al, 2005).…”
mentioning
confidence: 99%